Free anterolateral thigh flap and masseter nerve transfer for reconstruction of extensive periauricular defects: Surgical technique and clinical outcomes. Issue 6 (8th August 2016) - Cristóbal, Lara; Linder, Sora; Lopez, Beatriz; Mani, Maria; Rodríguez‐Lorenzo, Andres
Abstract: Background: Radical tumor ablation in the periauricular area often results in extensive soft tissue defects, including facial nerve sacrifice, bone and/or dura defects. Reconstruction of these defects should aim at restoring facial reanimation, wound closure, and facial and neck contours. We present our experience using free anterolateral thigh flap (ALT) in combination with masseter nerve to facial nerve transfer in managing complex defects in the periauricular area. Methods: Between 2011 and 2015 six patients underwent a combined procedure of ALT flap reconstruction and masseter nerve transfer, to reconstruct extensive, post tumor resection, periauricular defects. The ALT flap was customized according to the defect. For smile restoration, the masseter nerve was transferred to the buccal branch of the facial nerve. If the facial nerve stump was preserved, interposition of nerve grafts to the zygomatic and frontal branches was performed to provide separate eye closure. The outcomes were analyzed by assessing wound closure, contour deformity, symmetry of the face, and facial nerve function. Results: There were no partial or total flap losses. Stable wound closure and adequate volume replacement in the neck was achieved in all cases, as well as good facial tonus and symmetry. The mean follow‐up time of clinical outcomes was 16.8 months. Smile restoration was graded as good or excellent in four cases, moderate in one and fair in one. Conclusion: Extensive periauricular defects following oncologic resection could be adequately reconstructed in a combined procedure of free ALT flap and masseter nerve transfer to the facial nerve for smile restoration.